2016
DOI: 10.3892/mmr.2016.4817
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ischemic preconditioning reduces liver ischemia reperfusion injury in rats

Abstract: The aim of the current study was to investigate whether intestinal ischemic preconditioning (IP) reduces damage to the liver during hepatic ischemia reperfusion (IR). Sprague Dawley rats were used to model liver IR injury, and were divided into the sham operation group (SO), IR group and IP group. The results indicated that IR significantly increased Bax, caspase 3 and NF-κBp65 expression levels, with reduced expression of Bcl-2 compared with the IP group. Compared with the IR group, the levels of AST, ALT, MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…One study has executed IPC in the right hind limbs of rats with six cycles of pre‐condition clamping and reperfusion and has found that the attenuated liver necrosis is mediated by the up‐regulation of interleukin(IL)‐6 . In addition to remote IPC on limbs, intestinal IPC has also eliminated hepatic IR‐induced injury by decreasing inflammatory cytokines and enhancing Bcl‐2 expression . However, investigators also found that there was no additional protective effect of IPC in patients undergoing liver resection under continuous or intermittent vascular occlusion .…”
Section: Ipc For Attenuating Hepatic Ir Injurymentioning
confidence: 99%
“…One study has executed IPC in the right hind limbs of rats with six cycles of pre‐condition clamping and reperfusion and has found that the attenuated liver necrosis is mediated by the up‐regulation of interleukin(IL)‐6 . In addition to remote IPC on limbs, intestinal IPC has also eliminated hepatic IR‐induced injury by decreasing inflammatory cytokines and enhancing Bcl‐2 expression . However, investigators also found that there was no additional protective effect of IPC in patients undergoing liver resection under continuous or intermittent vascular occlusion .…”
Section: Ipc For Attenuating Hepatic Ir Injurymentioning
confidence: 99%
“…In animal studies, LIPC has been proven to be an efficient tool to protect most organs (e.g., liver, kidney, heart, and intestine), particularly via antioxidant pathway [ 4 ]. Concerning mechanism, a recent study demonstrates that LIPC can enhance a series of antioxidant genes' expression via activating cytoplasmic redox-sensitive transcription factors, effecting regulating cell redox status, inhibiting oxidative injury to cell components, altering the disturbance of Ca 2+ , and preventing nucleus injury and DNA fragmentation [ 5 ]. From bench to bedside, a randomized clinical trial (RCT) involves 60 liver donors by 10 min inflow occlusion and 10 min reperfusion to improve the graft tolerance to IRI, and the results indicate that LIPC approach significantly improves liver biochemical markers of hepatocyte function in deceased donor liver transplantation (LT) [ 6 ].…”
Section: Antioxidant Treatment For Donormentioning
confidence: 99%
“…Ischemic preconditioning (IPC) is a potent protective strategy in which a brief occlusion of ischemia and reperfusion results in tolerance to subsequent ischemia-reperfusion injury 8,9 . It has been demonstrated in multiple tissues and organs including the heart, liver, small intestine, and renal tissues [10][11][12][13] . Low-energy shock waves have been used in many fields to reduce the damage induced by tissue ischemia or to improve recovery after ischemia.…”
Section: ■ Introductionmentioning
confidence: 99%